Cancer Biomarkers and Targets in Digestive Organs - Lee, Nikki (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Identification and development of cancer biomarkers and targets have greatly accelerated progress towards precision medicine in oncology. Studies of tumor biology have not only provided insights into the mechanisms underlying carcinogenesis, but also led to discovery of molecules that have been developed into cancer biomarkers and targets. Multi-platforms for molecular characterization of tumors using next-generation genomic sequencing, immunohistochemistry, in situ hybridization, and blood-based biopsies have greatly expanded the portfolio of potential biomarkers and targets. These cancer biomarkers have been developed for diagnosis, early detection, prognosis, and prediction of treatment response. The molecular targets have been exploited for anti-cancer therapy and delivery of therapeutic agents. This Special Issue of Biomedicines focuses on recent advances in the discovery, characterization, translation, and clinical application of cancer biomarkers and targets in malignant diseases of the digestive system. The goal is to stimulate basic and translational research and clinical collaboration in this exciting field with the hope of developing strategies for prevention and early detection/diagnosis of cancer in digestive organs, and improving therapeutic and psychosocial outcomes in patients with these malignant diseases.